Pengaruh Pelatihan Komunikasi pada Supervisor terhadap Penurunan Stres Kerja Karyawan - Sari Natalia; Haryanto FR (JIP (Jurnal Intervensi Psikologi), 2010)
Purpose of this study is to investigate the impact of communication training for supervisors on employees occupational stress level in Antah Department Store Yogyakarta. There are 2 experiment groups, first consists of 4 supervisors who trained about communication and 18 subordinates who filled occupational stress scale pre, post 1 and post 2 training. Control group were 2 groups, first 5 supervisors were not be given training and 18 subordinates only asked to complete occupational stress scale pre, post 1 and post 2 training. By using anova mixed repeated measures, the result indicated that occupational stress level significantly decrease after their supervisors got communication training (F=15,839,p<0,01).Keywords: communication training, communication, occupational stress level